2017
DOI: 10.1111/aogs.13095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microbial invasion of amniotic cavity and the type of microorganisms on short‐term neonatal outcome in women with preterm labor and intact membranes

Abstract: Microbial invasion of the amniotic cavity by microorganisms other than Ureaplasma spp. was associated with earlier gestational age at admission and at delivery, and a higher rate of preterm delivery <24.0 weeks and of women who developed clinical chorioamnionitis. However, we did not find differences in the short-term neonatal outcome between women exposed to microbial invasion of the amniotic cavity and the no-microbial invasion of the amniotic cavity/no-intra-amniotic inflammation group delivering after 24.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
(70 reference statements)
1
29
0
Order By: Relevance
“…may effectively trigger adverse inflammatory monocyte responses, may considerably interfere with MMP-9 activity and, as a result, provoke subsequent pathologies. It is most likely that in vivo , pathogen virulence [ 19 , 84 ], microbial load [ 4 , 9 , 81 ], the duration of exposure [ 76 ], polymicrobial interactions [ 77 , 85 ], host genetics [ 78 ] and gestational age [ 33 , 80 , 81 ] all shape the clinical course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…may effectively trigger adverse inflammatory monocyte responses, may considerably interfere with MMP-9 activity and, as a result, provoke subsequent pathologies. It is most likely that in vivo , pathogen virulence [ 19 , 84 ], microbial load [ 4 , 9 , 81 ], the duration of exposure [ 76 ], polymicrobial interactions [ 77 , 85 ], host genetics [ 78 ] and gestational age [ 33 , 80 , 81 ] all shape the clinical course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated bacterial colonization of the amniotic fluid in both complicated and healthy pregnancies using culture-dependant and cultureindependent techniques. These studies have reported a diverse range of results, with some finding that amniotic fluid was devoid of bacteria (Rowlands et al, 2017), some finding that all amniotic fluid samples contain bacteria (Collado et al, 2016;Urushiyama et al, 2017;Wang et al, 2018;Zhu et al, 2018), and yet others reporting a combination of positive and negative samples (Watts et al, 1992;Mandar et al, 2001;Bearfield et al, 2002;Mendz et al, 2013;Cobo et al, 2017;Kayem et al, 2018;Lim et al, 2018;Morimoto et al, 2018;Stinson et al, 2019a). While pathogenic colonization of the amniotic fluid has been well-documented and thoroughly studied in the context of spontaneous preterm delivery (PTD; <37 gestational weeks) and fetal infection (DiGiulio, 2012;Mendz et al, 2013;Stinson and Payne, 2019;Thorell et al, 2019), little is known about the nature, origins, and significance of any endemic amniotic fluid bacteria in normal pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…clinical management. The antenatal management of women with PTL has been reported previously 47 and includes fetal maturation with a complete course of antenatal steroids (betamethasone) between 24.0 to 34.6 weeks and tocolysis (nifedipine or atosiban). Antibiotics (ampicillin, gentamycin, azithromycin) were prophylactically initiated in women with advanced cervical dilatation (Bishop index >6) and were discontinued if the amniotic fluid culture result was negative.…”
Section: Methodsmentioning
confidence: 99%